Cranial autonomic symptoms in episodic migraine: An observational study from headache clinic of a tertiary care center of North India - Qavi, Abdul; Maurya, Pradeep Kumar; Jasrotia, Rajani Bala; Singh, Ajai Kumar; Kulshreshtha, Dinkar; Ansari, Arshi; Thacker, Anup Kumar (Nepal Journal of Neuroscience, 2021)
Introduction: The presence of cranial autonomic symptoms (CAS) is a hallmark of trigeminal autonomic cephalalgia like cluster headache but their presence in migraine is also not uncommon. Like in trigeminal autonomic cephalalgias, the activation of the trigeminal autonomic reflex pathway is thought to be the possible explanation of the presence of cranial autonomic symptoms in migraine also. Previous studies suggested that around half of the patients of migraine suffer from these symptoms. The aim of our study was to observe the frequency of cranial autonomic symptoms in episodic migraine patients along with their clinical and autonomic characteristics. Methods and Materials: Fifty patients of episodic migraine attending the headache clinic of Dr. RMLIMS, Lucknow and fulfilling the diagnostic criteria of International classification of headache disorder third edition beta were randomly selected and enrolled in the study. The detailed interview regarding presence of cranial autonomic symptoms was recorded along with the clinical characteristics, demographic features and autonomic profile of the migraine patients. Results: About three-fourth (72%) of the patients were females. The mean age of study participants was 27.7±8.3 years. A considerable number of patients (54%) had a long duration (5-10 years) of illness and 70% of patients had severe headaches. Photophobia was the most common (88%) associated clinical symptoms while lacrimation was the most common (56%) cranial autonomic symptom in migraine patients. Among 50 patients of migraine 74% of patients were having at least one cranial autonomic symptoms. Conclusion: Cranial autonomic symptoms are common in patients of episodic migraine. More severe headache is more likely to be associated with the development of cranial autonomic symptoms.